Effects of bovine somatotropin injection on serum concentrations of progesterone in non-lactating dairy cows - Aboin, A. C. [UNESP]; Cooke, Reinaldo Fernandes [UNESP]; Vieira, F. V R [UNESP]; Leiva, T. [UNESP]; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier, 2013)
The objective of this experiment was to evaluate the effects of bovine somatotropin administration on serum concentrations of glucose, insulin, NEFA, IGF-I, and progesterone (P4) in ovariectomized non-lactating dairy cows receiving exogenous P4, as a model to estimate treatment effects on hepatic P4 degradation. Ten non-lactating, non-pregnant, and ovariectomized Gir×Holstein cows were assigned to the experiment (d -14 to 27). On d 0, cows were ranked by BW and BCS, and randomly assigned to one of two treatments: (1) bovine somatotropin (BST; n=5) or (2) saline control (control; n=5). Cows assigned to the BST treatment were administered s.c. injections containing 500. mg of sometribove zinc on d 0, 9, and 18 of the experiment, whereas control cows concurrently received a 10-mL s.c. injection of 0.9% saline. On d -2, cows were inserted with an intravaginal releasing device containing 1.9. g of P4, which remained in the cows until the end the experiment (d 27). Cow BW and BCS were assessed on d -14, 0, and 27. Blood samples were collected daily from d 0 to d 27, at 0 (immediately before), 1, and 2. h relative to concentrate feeding for determination of serum glucose, insulin, NEFA, P4, and IGF-I concentrations. Concentrations of glucose, NEFA, and insulin obtained prior to feeding (0. h) were used to determine pre-prandial revised quantitative insulin sensitivity check index (RQUICKI). No treatment effects were detected for BW (P=0.72) and BCS change (P=0.79) during the experiment. Beginning on d 2 of the experiment, BST cows had greater (P≤0.01) serum IGF-I concentrations compared with control cohorts (treatment×day interaction; P<0.01). Cows receiving BST had greater (P≤0.05) insulin concentrations compared with control cohorts from d 8 to d 11, d 16 and 17, as well as from d 19 to d 21 of the experiment (treatment×day interaction; P<0.01). Cows receiving BST had greater (P≤0.01) mean glucose and NEFA concentrations, as well as reduced (P<0.01) mean RQUICKI during the experiment compared with control cohorts. No treatment effects, however, were detected (P=0.73) for serum P4 concentrations. In conclusion, results from this experiment indicate that hepatic P4 catabolism is not directly regulated by circulating IGF-I, whereas BST administration decreases insulin sensitivity in non-lactating dairy cows in adequate nutritional status. © 2013 Elsevier B.V.
Keywords: Dairy cows; IGF-I; Insulin; Progesterone; Bos; Bovinae